Comparación de fuentes de grasa en la dieta de desarrollo para pollos de la línea Dekalb® White de 11 a 15 semanas de edad - Salinas N., Takarly F.; Vasquez R., Nilda M. (Zamorano: Escuela Agrícola Panamericana, 2025)
Zootecnia